DEVELOPMENT OF LOCAL COMPONENTS FOR FUEL CELL TECHNOLOGY - Eniya Listiani Dewi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
DEVELOPMENT OF LOCAL COMPONENTS FOR FUEL CELL TECHNOLOGY. The limitation of oil and gas, dependence of system using energy besides oil fuel, and also awareness of environmental friendly policy have become urgency of fuel cell research. Alternative energy becomes main priority development in the world. Not only in developed countries such as US, Japan, Europe and Canada, many developing countries in Asia are running up to catch the hydrogen used technology. Furthermore, Indonesian policy of energy are shown a requirement to develop on renewable energy and the primary energy mix (Perpres 5/2006, 25 Januari 2006, Kepmen ESDM No. 0983 K/16/MEM/2004, Kepmen ESDM No. 0002/2004, PP No. 03/2005 about change to PP No.89/1989). According to national research strategy, especially of hydrogen and fuel cell technology in 2009, manufacture and production technology, distribution, security of hydrogen and PEMFC technologies is needed. Indeed, in 2025 Indonesia must have national attached PEMFCs 50 kW and capacities goals of 250 MW. On the other hand, vehicle of fuel cell will step into market in the year 2010-2015. The market for mobile fuel cells, with DMFC technologies expected to account for a large portion, is projected to reach US 2.6 billion by 2012. Therefore, fuel cell technology is become a crucial technology including of opportunity of local component to contribute in manufacturing fuel cell technology and also a hydrogen storage technology systems. Herein we described the development of various components of fuel cell along with the process such as polyelectrolyte membrane of PEMFC and DMFC, bipolar plate and steam reforming methane with inorganic membrane in BPPT.